Modeling and simulation of a non-linear friction damper with full car model - Sharis-Shazzali bin Shahimi
A vehicle damping characteristics is shown to be nonlinear. An empirical investigation of a simple passenger full-car model is presented. Experiments are performed on a passive damper suspension and a friction damper to obtain the characteristics of a nonlinear damper, namely, the backbone of Force versus Velocity curves in which describes nonlinear effects that depend on varying frequencies and amplitudes of the road profile. This backbone curve is applied to determine the necessary nonparametric equations. Results using the experimental parameters and the simulation models are obtained so that comparisons with respect to the performance of the damper are made. A road profile is then used to simulate a quarter car models using these nonlinear equations. Analysis of the results includes vertical acceleration of the center of gravity of sprung mass of the model in a range of frequencies.